2019
DOI: 10.4168/aair.2019.11.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence of Allergic Rhinitis in China

Abstract: Allergic rhinitis (AR) is a critical public health, medical and economic problem in China. AR is also an important risk factor which will cause many diseases or disorders, especially in children. The trend of AR incidence is still on the rise in recent years and has had a significant effect on the general public. This significant increase is alarming, which highlights an urgent need for better understanding of the prevalence status and characteristics, sensitization patterns, and the associated risk factors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
122
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(134 citation statements)
references
References 64 publications
5
122
1
6
Order By: Relevance
“…Constrained by the lack of objective tests in the relative studies, the prevalence of chronic rhinitis, especially prevalence of NAR, is still unclear. Without doubt, the global prevalence of AR is markedly increasing over the recent years 11,12 . It is estimated that AR and NAR affect 20%-30% and 17%-52% of the population 10,[13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Constrained by the lack of objective tests in the relative studies, the prevalence of chronic rhinitis, especially prevalence of NAR, is still unclear. Without doubt, the global prevalence of AR is markedly increasing over the recent years 11,12 . It is estimated that AR and NAR affect 20%-30% and 17%-52% of the population 10,[13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Плохо контролируемый АР с выраженными симптомами представляет собой тяжелую хроническую болезнь верхних отделов дыхательных путей (severe chronic upper airway disease -SCUAD). АР обладает высокой коморбидностью и оказывает серьезное негативное влияние на качество жизни и социальную активность [1][2][3][4].…”
Section: практикаunclassified
“…Epidemiological studies have shown that AR affects at least half a billion people worldwide, and more than half of them suffer from moderate to severe AR [3]. In China, the prevalence of AR even rises to 34.3% of the general population, and rates still continue to increase [4][5]. Although without life threatening, AR exhibits negative in uence on people's quality of life and their work production, and brings about a high medical cost on both the individual and society.…”
Section: Introductionmentioning
confidence: 99%